Presence of asymptomatic cytomegalovirus and Epstein--Barr virus DNA in blood of persons with HIV starting antiretroviral therapy is associated with non-AIDS clinical events. (1st May 2020) - Gianella, Sara; Moser, Carlee; Vitomirov, Andrej; McKhann, Ashley; Layman, Laura; Scott, Brianna; Caballero, Gemma; Lada, Steven; Bosch, Ronald J.; Hoenigl, Martin; Lurain, Nell; Landay, Alan; et al.
Abstract : Background: Even with antiretroviral therapy (ART), persons with HIV (PWH) experience increased morbidity and mortality. Cytomegalovirus (CMV) and Epstein--Barr virus (EBV) co-infections likely exacerbate inflammatory-related diseases. Objective: To determine if presence of detectable CMV or EBV DNA in peripheral blood mononuclear cells (PBMC) is associated with non-AIDS events among PWH receiving modern ART. Design: We performed a case--control study of PWH starting ART and HIV-suppressed at year 1 and thereafter, 140 cases who experienced non-AIDS events and 305 matched controls. Events included myocardial infarction, stroke, malignancy, serious bacterial infection or death. Methods: Blood samples were studied pre-ART, 1-year post-ART and pre-event. Controls had an event-free follow-up equal or greater than cases. CMV and EBV DNA levels were measured in PBMC. Conditional logistic regression analysis assessed associations and adjusted for relevant covariates; Spearman's correlations compared CMV and EBV DNA levels with other biomarkers. Results: CMV DNA was detected in PBMC of 25% of participants, EBV DNA was detected in more than 90%. Higher EBV DNA levels were associated with increased risk of events at all time points (odds ratio (OR) per one IQR = 1.5–1.7, all P  < 0.009). At year 1, detectable CMV DNA was associated with increased risk of events in most adjusted models (OR = 1.4–1.8, P values ranging 0.03–0.17). Higher levels of CMV and EBV DNA correlated with multiple inflammatory markers and lower CD4 + /CD8 + ratio. Conclusion: In PWH starting ART, detection of CMV and EBV DNA in PBMC was associated with development of non-AIDS events. Clinical trials will be needed to understand causal mechanisms and ways to interrupt them. Abstract : Supplemental Digital Content is available in the text